The impact of the 2021 flood on the outpatient care in the North Rhine region, Germany: a cross-sectional study - Luca Theresa Wiesehahn; Andrea Kaifie (BMC, 2024)
Abstract Background In the summer of 2021, heavy precipitation led to extreme flooding across Western Europe. In Germany, North Rhine-Westphalia and Rhineland-Palatinate were particularly affected. More than 180 people lost their lives, and over 700 were left injured and traumatized. In the North Rhine district alone, more than 120 practices were only able to operate to a limited extent or had to close their practices completely. The aim of this study was to assess the impact of the 2021 flood on the outpatient care in the North Rhine region. Methods The cross-sectional study was conducted in January 2022 in practices affected by the flood in the North Rhine region. For this purpose, 210 affected practices were identified using a list of the Association of Statutory Health Insurance Physicians for North Rhine (KVNO) and via telephone and/or e-mail. These practices were forwarded a questionnaire that addressed, among other things, the local accessibility of the practices before and after the flood, possibilities of patient care in different premises and received support. Results A total of 103 practices (49.1%) returned the completed questionnaire, of which 1/4 were general practitioners. 97% of the practices reported power failure, more than 50% water supply damage and nearly 40% the loss of patient records. 76% of the participating practices stated that they needed to close their practice at least temporarily. 30 doctors took up patient care in alternative premises. The average number of patients seen by doctors per week before the flood was 206.5. In the first week working in alternative premises, doctors saw an average of 66.2 patients (-50.3%). Especially elderly/geriatric patients and patients with disabilities were identified as particularly vulnerable in terms of access to health care after the flood. Conclusions The flood had a significant negative impact on outpatient care. We determined not only a high number of closed practices and a large decrease in patient numbers but also differences in patient care assessment depending on the type of alternative premises. To address outpatient care disruptions after extreme weather events more effectively, appropriate measures should be implemented pre-emptively.